Improving interfacial properties and thermal conductivity of carbon fiber/epoxy composites via the solvent-free GO@Fe3O4 nanofluid modified water-based sizing agent. (16th June 2021) - Cheng, Chunxia; Zhang, Mengjie; Wang, Siyu; Li, Yushi; Feng, Hengyu; Bu, Danlin; Xu, Zice; Liu, Yong; Jin, Lin; Xiao, Linghan; Ao, Yuhui
Abstract: In order to address the less-than-satisfactory interfacial properties and thermal conductivity of carbon fiber reinforced polymers (CFRPs), a general solvent-free GO@Fe3 O4 nanofluid (GFNF) hybrid water-based sizing agent was prepared and applied for carbon fiber (CF) sizing. A discussion was conducted about the effects of different GFNF contents on the CF/epoxy composites (CF/EP) for their interfacial properties and thermal conductivity. In comparison with the composites made up of commercial CF and epoxy, the interfacial and thermal conductivities of the GFNFCF/EP composites were significantly improved. Notably, the increase in 2.5-GFNFCF/EP was most noticeable, with ILSS and flexural strength improved by 15% and 43.6%, respectively. This is attributed to the uniform adhesion of GFNF to the CF surface, which enhances the physical-chemical interaction of fiber with matrix, promotes the dispersion of stress, and prevents cracking from spreading. Also, the thermal conductivity was improved by 128.9% due to the formation of continuous thermal conduction pathways at the interface. The mechanism behind interface and thermal conductivity enhancement of the composites was proposed. This hybrid sizing agent contributed a different solution to improving the interfacial properties and thermal conductivity of CFRPs at the same time. Graphical abstract: Image 1